1996
DOI: 10.1524/anly.1996.16.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of Exterior Problems. Optimal Conditions for the Laplacian.

Abstract: For an exterior domain Ω C M", ri > 3 with smooth boundary dil let u be a solution of the exterior boundary value problem -Δω = / in Ω, u = g on 0Ω. Let GR be a set of bounded domains which contain dil for any R and exhaust Ω as R -ν oo. The following approximation problem is considered: -Au R = f in GR Π Ω, u R = g on dil, B(χ, V)u R = 0 on 8GR. By using formal asymptotic formulae for u R it turns out that among the possibilities Dirichlet condition, Neumann condition and mixed condition the latter one leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 6 publications
(8 reference statements)
3
23
0
Order By: Relevance
“…For the most part, these methods are equivalent. In the required generality, the problem about a small cavity or inclusion was studied with the help of one or the other method in [37,38,9,39], and simple examples were considered in [37,40,8,41] and other publications. Therefore, the result of the asymptotic analysis of the energy functional (2.8) will be formulated below without accompanying calculations and the justification procedure, but with only brief explanations in Remarks 6.1 and 6.2.…”
Section: An (N × N )-Matrix Amentioning
confidence: 99%
“…For the most part, these methods are equivalent. In the required generality, the problem about a small cavity or inclusion was studied with the help of one or the other method in [37,38,9,39], and simple examples were considered in [37,40,8,41] and other publications. Therefore, the result of the asymptotic analysis of the energy functional (2.8) will be formulated below without accompanying calculations and the justification procedure, but with only brief explanations in Remarks 6.1 and 6.2.…”
Section: An (N × N )-Matrix Amentioning
confidence: 99%
“…Such approximations of unbounded problems by bounded ones are currently used (see e.g. [1,5,8] and references therein), and we must provide a condition on the boundary of the outer truncated domain.…”
Section: Practical Implementation -Truncation Of the Domainmentioning
confidence: 99%
“…These three boundary conditions are discussed for instance, in [8] (see also the discussion in [1] for the Helmholtz equation) where it is shown that for the Laplace equation with a right hand side which is non compactly supported, the Neumann boundary conditions might give a solution which does not converge as the outer boundary goes to infinity and that the mixed boundary condition is better than the Dirichlet.…”
Section: Practical Implementation -Truncation Of the Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Their choice is based on the asymptotic behavior of solutions at infinity. In particular, for elliptic boundary value problems in exterior domains and domains with cylindrical or conical outlets to infinity, ABCs in differential form were systematically developed during the last decades (see e.g., [1,2,4,5,7,9,10,14,23,24,32,34]) and the papers quoted there.) The common feature of local ABCs are estimates for the truncation error of the form u ∞ − u R = O(R −γ ) as R tends to infinity, with some γ > 0.…”
Section: Introductionmentioning
confidence: 99%